The Level Living of Wife's Iddah According to The Judge's Ijtihad Makassar Religious Court Class 1A - P, Umar; HT, Abd. Qadir Gassing; Supardin, Supardin (Jurnal Diskursus Islam, 2023)
The aims of this study are: 1) to find out the legal basis for ijtihad judges at the Makassar Religious Court Class 1A in determining the level of post-divorce wife iddah. (2) to find out the difference between the level of iddah of a career wife and a non-career wife. 3) to find out the judge's efforts in ensuring the implementation of a decision. This type of research is classified as field research (Descriptive Qualitative Field Research) and uses a formal juridical approach, sociological empirical and sharia approach. The data source of this research is Makassar Religious Court Judge Class 1A. Furthermore, the data collection methods used were literature review, observation, and interviews. Then there are three stages of data management and analysis, namely, data collection, data processing and drawing conclusions from the research results. The results of this study indicate that 1) In the study of determining the amount of iddah of the wife to be given to the wife, the panel of judges used the Qur'an and hadith, as well as SEMA No. 7 of 2012 which was later refined by SEMA No. 3 of 2018 as the legal basis for the criteria for determining the amount of the wife's iddah. 2) As for the problem of a wife who has a career or has a job status, it is very necessary to be made a judge as one of the factors in determining the amount of the iddah living value. 3) And the efforts made by the judge to ensure the implementation of a decision, namely the postponement of the pronouncement of the divorce pledge and the detention of the husband's divorce certificate in the case of a contested divorce. The implications of this research are 1) For judges, presumably they can make the status of the wife as one of the factors to determine a decision and maximize the efforts made so that the decision can be carried out by the husband, especially in cases of divorce and litigation and the imposition of iddah maintenance on the husband for the result of a divorce. 2) For the community, one of the consequences of a divorce is that the husband is obliged to provide iddah to his wife as stated in article 149 of the Presidential Instruction on the Compilation of Islamic Law. 3) For further researchers, if you are interested in conducting similar research, it would be better to use a different research method, as well as conduct research related to other factors that are considered capable of providing other views in terms of determining the level of iddah living.